(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The purpose of this study is to determine the housekeeping practices that affect customer satisfaction in the Bellevue Hotel in Timog Quezon City. The results of this study reveal that the hotel is doing a great job in providing guest satisfaction to the customers where the respondents described the housekeeping practices of the hotel in terms of cleanliness of the guest rooms, efficiency of the services offered, and waste management as strongly satisfying. Customer satisfaction in terms of room ambiance, security services, and facilities was assessed as highly observed. This study recommends that the hotel maintain the quality of the processes that ranked with the highest satisfaction and observation except for the two: speed of delivery of loaned items and waste disposal, where the study found that customers had the lowest satisfaction level.